The Products of Probiotic Bacteria Effectively Treat Persistent Enterococcus faecalis Biofilms - Shatha Safadi; Harsh Maan; Ilana Kolodkin-Gal; Igor Tsesis; Eyal Rosen (MDPI AG, 2022)
Objectives: Enterococcus faecalis is a Gram-positive commensal bacterium that possesses various survival and virulence factors, including the ability to compete with other microorganisms, invade dentinal tubules, and resist nutritional deprivation. E. faecalis is associated with persistent endodontic infections where biofilms formed by this bacterium in the root canal frequently resist dental therapies. Aseptic techniques, such as the inclusion of sodium hypochlorite, are the most commonly used methods to treat E. faecalis infections within the root canal system. In this work, we assess the effectiveness of probiotic strains to prevent the regrowth of E. faecalis biofilm cells treated by sodium hypochlorite irrigation. Methods: First, methods are presented that evaluate the effects of short-term exposure to sodium-hypochlorite on established E. faecalis. Next, we evaluate the effects of the secreted products of probiotic strains on biofilm cells and planktonic cells. Results: Sodium hypochlorite, the treatment conventionally used to decontaminate infected root canal systems, was extremely toxic to planktonic bacteria but did not fully eradicate biofilm cells. Furthermore, low concentrations of sodium hypochlorite induced eDNA dependent biofilms. Strikingly, conditioned medium from the probiotic bacteria Lactobacillus plantarum and Lactobacillus casei was sufficient to fully prevent the regrowth of treated biofilms while showing reduced potency towards planktonic cells. Conclusion: Sodium hypochlorite irrigations may contribute to the persistence of biofilm cells if used at concentrations lower than 3%. Probiotic strains and their products represent a new reservoir of biofilm therapies for E. faecalis infections formed in the root canal system.